PERLINDUNGAN HUKUM DARI PT ASURANSI KERUGIAN JASARAHARJA PUTERA TERHADAP WISATAWAN YANG MENGALAMI KECELAKAAN DI BALI - Cahya Sri Widari, A. A. Sg Istri; Markeling, I Ketut; Dedy Priyanto, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014)
In tourist traveling in indonesia in Bali becomes very important. It involves the safety of your tour. such conditions has earlier handled by travel agency. Travelers against accidents often occur especially at tourist object in Bali, especially in tourism activities. Relationsship between PT insurance Jasaraharja with travel agents in carrying out this insurace agreement basically describes the rights and obligations between the two parties. parties commited themselves to indemnify or pay the premiums to the insurer. Which this paper titled legal protection of PT insurance jasaraharja putera towards tourists who had an accident in Bali. This paper aims to understand the form of legal protection. The results showed that the PT insurace Jasaraharja Putera so its easier to get right to lighte the conditions to be met by travel to obtain compensation or redress. Study is a form of research data interview the data directly on an agency or institution wich is the object of research.
Keywords: protection, Insurance, compensation